Persepsi Guru Terhadap Aspek Penilaian Sikap dan Aspek Penilaian Keterampilan dalam Kurikulum 2013 Di Sekolah Dasar - Eko Kuntarto; Putri Susanti (Jurnal Gentala Pendidikan Dasar, 2016)
The purpose of this study is to describe the views of teachers on aspects of attitude assessment and aspects of skills assessment which after the implementation of Permen No 53 Year 2015 is very well looked at by teachers from the old regulations. The research method is qualitative descriptive research. This research was conducted at SDN 55/1 Sridadi, class I of the 2016 school year, namely in 2 first-class guardian teachers. Data obtained from the results of questionnaires, and semi-structured interviews. The results of the study describe the views of teachers on aspects of attitude assessment and aspects of skills assessment which after the implementation of Regulation No. 53 of 2015 was very well looked at by the teacher from the old regulations. The results of interviews in a structured way are obtained by the opinion of the teacher agreeing / good towards the new revision and the overall results of the distribution of the teacher questionnaire are already in a very good stage of understanding. So the teacher's perception of the new assessment system is good because the teacher can easily understand the implementation and implementation of the 2013 Curriculum with the issuance of Permen No 53 year 205, but the teacher still has problems in processing student grades which are considered complicated. Therefore, further training needs to be done so that the teacher's understanding of the assessment in the 2013 curriculum gets better.